2016
DOI: 10.1002/pon.4286
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of collaborative care interventions for depression in patients with cancer

Abstract: Collaborative care interventions have newly emerged as multidisciplinary care delivery models, which may result in more long-term depression remission. This review also updates previous findings of modest evidence for the effectiveness of both pharmacological and psychological interventions for threshold depression in cancer patients. Research designs focusing on combined treatments and delivery systems may best further the limited evidence-base for the management of depression in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 68 publications
(336 reference statements)
1
96
0
4
Order By: Relevance
“…We should, however, query the claim for CCIs working in “active collaboration” with primary and specialist oncology care. In SMaRT‐2, the majority (79%) of enrolled patients were post‐acute (in remission and follow‐up), at which point community and primary care services should arguably be increasingly relevant and involved in meeting survivors' needs.…”
Section: Reviewing Collaborative Care Interventions: It Is Not Just Tmentioning
confidence: 99%
See 1 more Smart Citation
“…We should, however, query the claim for CCIs working in “active collaboration” with primary and specialist oncology care. In SMaRT‐2, the majority (79%) of enrolled patients were post‐acute (in remission and follow‐up), at which point community and primary care services should arguably be increasingly relevant and involved in meeting survivors' needs.…”
Section: Reviewing Collaborative Care Interventions: It Is Not Just Tmentioning
confidence: 99%
“…The weight of this review, then, and how it leaves out context and related concepts such as distress and adjustment disorder may inadvertently risk amplifying a drifting tide, a narrowing perspective away from a person-centred psycho-oncology that can be valid, helpful, and necessary without resorting to undue medicalisation of distress. We should, however, query the claim for CCIs working in "active collaboration" 18 with primary and specialist oncology care. In SMaRT-2, 15 the majority (79%) of enrolled patients were post-acute (in remission and follow-up), at which point community and primary care services should arguably be increasingly relevant and involved in meeting survivors' needs.…”
Section: Depression Nothing But Depressionmentioning
confidence: 99%
“…[5][6][7] More recently, three systematic reviews of randomized controlled trials (RCTs) confirmed that psychotherapy is effective in treating depressive states in individuals with advanced cancer, despite methodological limitations in most studies. [8][9][10] Both Dignity Therapy, 11 a legacy-building intervention for those near the very end of life, and Meaning-Centered Psychotherapy, 12,13 a group or individual intervention that promotes a sense of meaning and purpose in patients with advanced cancer, have been shown to be effective in a variety of outcomes. [13][14][15] We have developed a novel, brief, tailored supportiveexpressive psychotherapeutic intervention, referred to as Managing Cancer And Living Meaningfully (CALM) for patients with advanced cancer and a prognosis of at least 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to evaluate of the effect of detection, treatment, treatment paradigm, timing, and quality of life improvement along with quantifying the economic impact of treatment on health care costs and service use. As the US health care system potentially moves toward a more interdisciplinary care model, collaborative care interventions for depression may be the key to deliver significant positive long‐term impact in terms of quality of life and reduced health care service use and costs …”
Section: Discussionmentioning
confidence: 99%
“…As the US health care system potentially moves toward a more interdisciplinary care model, collaborative care interventions for depression may be the key to deliver significant positive long-term impact in terms of quality of life and reduced health care service use and costs. 32…”
Section: Discussionmentioning
confidence: 99%